1982
DOI: 10.1017/s0016672300020930
|View full text |Cite
|
Sign up to set email alerts
|

Non-random X-chromosome inactivation in the mouse: difference of reaction to imprinting

Abstract: Selection for increased and for decreased expression of the sex-linked gene brindled (Mo br ) in heterozygous females produced two lines with non-random X chromosome inactivation. In the High line the X chromosome marked by brindled was active in about 60 % of cells, while in the Low line it was active in about 25 % of cells. The whole of the difference was caused by the chromosomes carrying brindled: neither the unmarked X chromosome nor the autosomes were differentiated. There was a positive correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
3
10
1
Order By: Relevance
“…X M and X p may have an equal probability of becoming inactivated (Johnston & Cattanach, 1981) or in some circumstances X p may be preferentially expressed (Falconer et al 1982). Using PGK-1 alloenzyme expression in erythrocytes, we have found parental effects on X chromosome expression using one allelic combination of Xce genes but no such effects with another.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…X M and X p may have an equal probability of becoming inactivated (Johnston & Cattanach, 1981) or in some circumstances X p may be preferentially expressed (Falconer et al 1982). Using PGK-1 alloenzyme expression in erythrocytes, we have found parental effects on X chromosome expression using one allelic combination of Xce genes but no such effects with another.…”
Section: Discussionmentioning
confidence: 81%
“…Some studies indicate a 'paternal' effect i.e. X p has a higher probability of remaining active than X M (Falconer, Isaacson & Gauld, 1982), while others show no significant reciprocal cross differences (Johnston & Cattanach, 1981). In selection experiments with the X-linked gene brindled (Mo br ) (Falconer et al 1982) and viable brindled (Mo vbr ) (Cattanach & Papworth, 1981), a positive correlation was observed between the expression of brindled in mothers and daughters.…”
Section: Introductionmentioning
confidence: 99%
“…X p having a higher probability of remaining active (Cattanach, 1975;Falconer et al 1982). In selection experiments with the X-linked brindled alleles Falconer et al (1982) and Cattanach & Papworth (1981) found a positive correlation between the expression of brindled in mothers and daughters. However, this 'maternal' effect was attributed to a physiological difference rather than the parental origin of the chromosome.…”
Section: Resultsmentioning
confidence: 96%
“…Some authors have found no reciprocal cross differences (Johnston & Cattanach, 1981) while others demonstrate a 'paternal' effect, i.e. X p having a higher probability of remaining active (Cattanach, 1975;Falconer et al 1982). In selection experiments with the X-linked brindled alleles Falconer et al (1982) and Cattanach & Papworth (1981) found a positive correlation between the expression of brindled in mothers and daughters.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the well-known examples of paternal-X inactivation in extraembryonic membranes of some eutherian females, including mice, rats, and cattle (Takagi and Sasaki 1975;Wake et al 1976;West et al 1977;Harper et al 1982;Xue et al 2002;Wagschal and Feil 2006), in preimplantation rodent embryos (Latham 2005) and somatic tissues of kangaroos and other marsupials (Sharman 1971;Graves 1996, Johnston et al 2002, there is also evidence of such phenomena in the somatic tissues of eutherian mammals. Preferential inactivation of the maternally derived X chromosome (rather than the usual pattern of random inactivation; Graves 1996) has been observed in the somatic cells of female mice (Cattanach and Perez 1970;Falconer and Isaacson 1972;Falconer et al 1982). More circumstantially, Hunt (1991) demonstrated that the viability of female mice with only one X chromosome was lower in mice whose X chromosome was paternally derived, suggesting that a number of genes relating to fitness may be expressed exclusively from the maternally inherited X chromosome.…”
mentioning
confidence: 99%